Study of the process of the frozen raw beef defrosting with its simultaneous massaging in industrial conditions - N. S. Nikolaev; V. N. Kornienko (Теория и практика переработки мяса)
Many meat processing enterprises use the frozen raw meat. Its defrosting and thawing is a crucial technological operation that fundamentally affects the quality of food products. The experience and knowledge obtained directly in the workshop in the process of thawing the raw materials and their using to obtain a specific finished product are of great importance. Defrosting and thawing of the frozen beef meat, as one of the stages of raw meat processing, still remains a challenging process in industrial food production. The importance of this process is constantly increasing due to the growing volumes of frozen raw materials processed in food enterprises. Scientific research shows that one of the most efficient methods of defrosting and thawing is the process of meat thawing with saturated water steam under vacuum. When applying the steam the raw materials is heated at its least and minimal losses are observed, while the duration of the process is significantly reduced. This work examines the process of beef meat defrosting and thawing with simultaneous shaking and crumpling the frozen mass, which can be called as massaging of raw materials. As studies have shown, this method of thawing makes it possible to reduce losses down to almost zero and obtain raw materials with good structural characteristics for the production of a finished product with a wide range of consumer properties. The obtained experimental curves of changes in the mass and temperature of raw materials make it possible to analyze the kinetics of heat transfer and mass transfer processes at the macro- and micro levels of the food system, which serve as the basis for modeling and controlling the technological process. This study presents the results of conventional defrosting and thawing of the raw meat but combined with massaging. Studies of the parameters of processing modes have shown that the proposed program makes it possible to use efficiently the design and technological features of the defroster-massager in order to obtain the raw beef for the production of high-quality food products. The results of experimental studies and their analysis allow making conclusion about the prospects of applying this process for the other types of raw meat materials before the main technological processing of raw materials.